Effects of physical exercise on coronary health, stroke risk, and blood pressure management - Zhu, Hao; Li , Yang; Tan, Zhaowen; Liu, Yaowen; Qian, Haonan (Molecular & Cellular Biomechanics, 2025)
Background: Mendelian randomization (MR) is a powerful tool. This method has garnered attention for its potential to circumvent the limitations of observational studies, such as confounding factors and reverse causation. In this study, we aimed to explore the causal effect of physical exercise on cardiovascular health using MR analysis. Methods: We used genetic variants strongly linked to physical exercise as instrumental variables from large-scale Genome-Wide Association Study (GWAS), based on data from over 300,000 European individuals in the UK Biobank. Exercise levels were measured through self-reports and accelerometer data, while cardiovascular outcomes were assessed using medical records, biomarkers, and imaging. Results: Demonstrated a significant causal relationship between higher levels of physical exercise and improved cardiovascular health outcomes. Specifically, an increase of one standard deviation in genetically predicted physical exercise was associated with a substantial reduction in the risk of coronary artery disease (OR: 0.75, 95% CI: 0.65–0.86, p < 0.001), stroke (OR: 0.80, 95% CI: 0.69–0.93, p = 0.004), and hypertension (OR: 0.82, 95% CI: 0.74–0.91, p < 0.001). Conclusions: Our findings provide strong evidence for a causal relationship between physical exercise and improved cardiovascular health. This study underscores the potential of physical exercise as a modifiable risk factor for cardiovascular disease and highlights the importance of incorporating physical exercise into public health interventions aimed at reducing cardiovascular risk. Future research should focus on identifying the mechanisms underlying this relationship and developing targeted strategies to increase physical exercise levels across populations.